2014
DOI: 10.3747/pdi.2011.00152
|View full text |Cite
|
Sign up to set email alerts
|

Does Body Fat Mass Define Survival in Patients Starting Peritoneal Dialysis?

Abstract: ♦ Background and Aims: Peritoneal dialysis (PD) is characterized by a gain in fat mass. Unlike subcutaneous fat, visceral fat is associated with metabolic syndrome and survival. We prospectively examined whether visceral or subcutaneous fat could predict outcome in patients undergoing PD. ♦ Methods: We studied 117 new patients (57 men) undergoing PD between February 2006 and November 2011. Baseline body composition was measured on computed tomograms. Visceral obesity was defined as a visceral fat area exceedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In a prospective study of 183 Chinese PD patients, abdominal fat was not associated with clinical outcomes such as CVD events or mortality 33) . In another prospective observational study with 117 Korean PD patients, increased abdominal fat at PD initiation was not a risk factor for poor outcome 34) .…”
Section: Discussionmentioning
confidence: 90%
“…In a prospective study of 183 Chinese PD patients, abdominal fat was not associated with clinical outcomes such as CVD events or mortality 33) . In another prospective observational study with 117 Korean PD patients, increased abdominal fat at PD initiation was not a risk factor for poor outcome 34) .…”
Section: Discussionmentioning
confidence: 90%
“… 21 , 22 A recent report concluded that increased visceral fat at the initiation of PD is not an independent predictor of poor survival. 23 In our study, we demonstrated that an increase in visceral fat is associated with a higher level of inflammation, which, in turn, may be associated with the development of LVDD and a worse prognosis. Based on the findings of our present and previous studies, 6 , 8 we may suggest that the effects of visceral fat on worsening prognosis are at least partially through increasing inflammation, and thereby, the development of LVDD.…”
Section: Discussionmentioning
confidence: 48%
“…This provides a further confirmation of the effectiveness of the educational intervention. These improvements in physical examination findings would have a positive impact on these patients' prognosis as reported by Choi et al (2014) in their study in Korea.…”
Section: Discussionmentioning
confidence: 63%